2020
DOI: 10.1158/1078-0432.ccr-19-3089
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Immunologic Characterization of INI1-Deficient Pediatric Cancers

Abstract: The prognosis for patients with INI1-deficient pediatric cancers is poor and therapeutic options, particularly in the relapsed or refractory setting, are limited. We sought to characterize the association between SMARCB1 genetic variants identified by next-generation sequencing and INI1 protein expression and to evaluate PD-L1 and CD8 expression in INI1-deficient tumors. Available evidence suggests a low rate of PD-L1 expression and response to immune checkpoint blockade in pediatric cancers. INI1-negative ped… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…15,16 These types of gastric cancers are also enriched for PD-L1 expression in comparison with other types. [17][18][19][20] On the basis of our findings, when these morphologies are encountered, NGS and PD-L1 tumor testing should be recommended. Morphologic-molecular correlation also confirmed the previously reported driver mutation genes in each histologic type.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…15,16 These types of gastric cancers are also enriched for PD-L1 expression in comparison with other types. [17][18][19][20] On the basis of our findings, when these morphologies are encountered, NGS and PD-L1 tumor testing should be recommended. Morphologic-molecular correlation also confirmed the previously reported driver mutation genes in each histologic type.…”
Section: Discussionmentioning
confidence: 82%
“…Notably, recognition of these uncommon WHO types based on morphology alone is challenging; undifferentiated carcinoma can be misinterpreted as the poorly cohesive type, and adenocarcinoma with enteroblastic differentiation can be misinterpreted as the tubular type 15,16 . These types of gastric cancers are also enriched for PD‐L1 expression in comparison with other types 17‐20 . On the basis of our findings, when these morphologies are encountered, NGS and PD‐L1 tumor testing should be recommended.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, we and others have reported in vivo responses to ICB for such tumors both in mice 9 and in humans 10‐12 . Importantly, no differences in TMB were identified between PD‐L1–positive and PD‐L1–negative SMARCB1‐deficient tumors in an independent cohort of pediatric patients 13 . As in RTs, a comprehensive study of RMC samples reported that although these tumors had a very low single‐nucleotide variant burden (a median of 24 single‐nucleotide variants per patient), they were still infiltrated by both lymphoid and myeloid cells, and they were recurrently positive for PD‐1 and PD‐L1 expression by immunohistochemistry 14 .…”
Section: Swi/snf Mutations Can Evoke a Targetable Immune Response In mentioning
confidence: 65%
“…The combination of radiation therapy with ICB thus represents an interesting therapeutic perspective currently under investigation 54 . Two cases involving SMARCB1‐deficient epithelioid sarcoma and UC have recently been reported as demonstrating partial long‐lasting responses to ICB either in combination with or after radiation therapy regimens 13 …”
Section: Clinical and Biological Implications Raised By Immune Systemmentioning
confidence: 99%
“…Regardless of the fact that little is known about the penetrance of non-rhabdoid SMARCB1-deficient tumors in RTPS, it has been generally accepted that any rare cancer in childhood justifies discussion and referral to genetic testing. More evidence from accumulated data will help to establish the clinical and thus individual benefit in the future [51][52][53][54].…”
Section: Should We Test Patients With Smarcb1-deficient Non Rhabdoid Tumors?mentioning
confidence: 99%